Pengembangan Lembaran Kerja Siswa (LKS) Ekperimen Berbasis Guided-Inquiry Materi Laju Reaksi Untuk Siswa SMA / MA - Andromeda, Andromeda; Yerimadesi, Yerimadesi; Iwefriani, Iwefriani (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
This study aims to produce teaching materials based material reaction rate guided inquiry (learning cycle: the phase of exploration, discovery / establishment of the concept and application) in the form of a valid experiment worksheets and practical use in learning chemistry in SMA / MA. This type of research included in Research and Development (R & D). The development model used in this study is the four-D (4-D). The research instrument is the validation sheet and questionnaire. Data from the study consists of three aspects, namely, the validity, the practicalities and effectiveness of teaching materials. Data validity and practicalities processed using Cohens Kappa formula, and the effectiveness of data using a percentage In this study is limited to the validity and practicalities. Validation of teaching materials from the aspect of content, language and graffiti and feasibility of construction. Data from the validator obtained an average score moment kappa was 0.87, and the results of practical analysis conducted with a limited test in MAN 3 Padang obtained an average score of 0.84 practicality value of 0.78 of teachers and students. From the analysis worksheets that showed 86 % of students working on critical questions and exercises contained in LKS experiments that have been made can be answered students. These results indicate that LKS guided inquiry-based experiments developed extremely valid and practical use in learning chemistry